Optimalisasi Manajerial Ekonomi Pada Koperasi Desa Mekarmukti Cikarang Utara Untuk Peningkatan Masyarakat - Eliza Kotrun Nada; Muh Arham Aswad; Nisah Ukhfi Angreani; Siti Khoirunnisa; Etty Zuliawati Zed (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2025)
Village cooperatives have a strategic role in driving local economic growth and improving community welfare. However, suboptimal managerial management is often a major obstacle in achieving these goals. This study aims to analyze and identify strategies to optimize economic managerial in village cooperatives in Melarmukti Village, North Cikarang District. The method used is a descriptive qualitative approach through observation, interviews with cooperative administrators, village officials, and local communities. The results showed that cooperatives in Melarmukti Village still face various challenges, such as the lack of managerial training, the lack of periodic evaluations, and low collaboration with external parties. Optimization can be done through increasing the capacity of cooperative human resources, implementing a periodic evaluation system, and establishing strategic partnerships with financial institutions and universities. With targeted and sustainable managerial improvements, village cooperatives have great potential to become economic drivers and improve community welfare at the local level.